Risk factors associated with pregnancy loss after single euploid blastocysts transfer - Dong, Xiaohui; Shi, Juanzi; Liu, Xiaohua; Liu, Danmeng; Li, Wei; Zhao, Xiaoli; Xue, Xia (Frontiers in Endocrinology, 2025)
ObjectiveTo detect primary factors influencing pregnancy loss(PL) following the transfer of euploid blastocysts?DesignRetrospective cohort study.MethodsTo identify potential factors influencing PL, we analyzed multiple variables in both the PL group and the live birth group. In order to minimize the impact of confounding factors, various variables were included in a binary logistic regression analysis.ResultsThe PL rate after the transfer of euploid embryos is 13.3% (36 cases of PL out of 270 cases of single embryo transfer). Compared to the live birth group, the PL group had lower E2 levels (2376.03 ± 1553.25 vs 3412.88 ± 2116.47, P=0.007), higher LH levels (2.66 ± 2.47 vs 1.96 ± 1.52, P=0.023) on trigger day of fresh cycle, fewer retrieved oocytes (10.08 ± 5.01 vs 12.77 ± 7.20, P=0.044), higher female BMI (23.26 ± 3.27 vs 22.05 ± 2.69, P=0.016), higher proportion of maternal smokers (50% vs 20.51%, P<0.001), and more day 6 blastocyst transfers ((38.89% vs14.53, P=0.001). Logistic regression analysis revealed that higher LH levels(OR=1.304, 95%CI=1.054-1.613, P=0.015), low E2 levels (OR=0.438, 95%CI=0.242-0.794, P=0.007) on trigger day of fresh cycle, maternal smoking(OR=4.574, 95%CI=1.974-10.601, P<0.001), and day 6 blastocyst transfer(OR=4.610, 95%CI=1.907-11.141, P=0.001) appeared to be associated with increased risk of PL following the transfer of euploid embryos.ConclusionsMaternal smoking, day of blastocyst transferred, estradiol (E2) and Luteinizing hormone (LH) levels on trigger day of corresponding fresh cycle for transferred blastocysts are all associated with PL following transfer of euploid embryos.